Financial statement analysis of Sarawak Plantation Berhad / Ayatullah Sapawi… [et al.] - Sapawi, Ayatullah; Nawawi, Rafidah (2014)
The aim of this paper is to analyze the audited financial statements of Sarawak Plantation Berhad using financial ratios analysis to identify potential problems areas of the company. Horizontal analysis or trend analysis and cash flow analysis would also be done to support the findings ofthe financial ratio analysis. Based on the problem identified, structured interviews were conducted to further clarify on the problems areas identified from the financial ratio analysis, horizontal analysis and cash flow analysis. Recommendations would also be made to the management of Sarawak Plantation Berhad based on the results and findings of the financial ratios analysis, horizontal analysis, cash flows analysis and the structured interviews. It is hopes that the findings and the recommendations made would help Sarawak Plantation Berhad, to improve its financial performance and also encourage more in-depth research to be done based on the findings ofthis study.